MAJĀZ DAN IMPLIKASINYA TERHADAP INTERPRETASI HADIS DIBELENGGUNYA SETAN DI BULAN RAMADHAN (Studi Takhrīj dan Ma’āni al-Hadīs) - Fajar Rachmadhani; Chalimatus Sa’adah (Diroyah : Jurnal Studi Ilmu Hadis, 2019)
The purpose of this research is to discuss the role of the connotation meaning (majāz) on the interpretation of the hadith which speak of being shaken by Satan in Ramadan. By focusing on library research, researchers try to trace all the hadiths that are related to the reign of Satan in Ramadan, then to understand the hadith this study specifically uses the study of ma'āni al-hadis with a lingusitic and confirmative approach . The practical benefits of this study are expected to provide encouragement and motivation for Muslims to always study the vast treasures of Islamic science, especially in the study of ulumul hadith. This type of research includes qualitative research, the main source of which is the kutub at-tis'ah (nine main books of hadith), while the secondary sources are information contained in journals, web sites, and others.